2015
DOI: 10.4172/2155-6199.1000272
|View full text |Cite
|
Sign up to set email alerts
|

Biotransformation of Nitro Aromatic Compounds by Flavin-Free NADHAzoreductase

Abstract: Nitro aromatic compounds are the potential toxic organic pollutant released into the environment and are often resistant to degradation under normal environmental conditions. The biotransformation and/or detoxification of these compounds can be possible by microbial azoreductase enzyme. Azoreductase enzyme has an ability to reduce the toxic nitro group to corresponding amino group. In present report, the flavin-free NADH azoreductase was isolated and purified from alkaliphilic bacteria Bacillus badius. The enz… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 11 publications
(4 citation statements)
references
References 22 publications
0
4
0
Order By: Relevance
“…The bacterial genera Clostridium sp., Eubacterium sp., Clostridium leptum , C. paraputrificum , C. perfringens , and C. clostridiiforme exhibited nitroreductase and azoreductase activities in the human GI tract [ 101 – 104 ]. Misal and Gawai have classified azoreductase superfamily into five different groups, depending upon their preference for nicotinamide and flavin: (1) flavin-containing NADPH-dependent azoreductase [ 105 , 106 ], (2) flavin-containing NAD(P)H-dependent azoreductase [ 107 110 ], (3) flavin-containing NADH-dependent azoreductase [ 111 , 112 ], (4) flavin-containing NAD(P)H-dependent quinine oxidoreductases [ 113 , 114 ], and (5) flavin-free NAD(P)H-dependent azoreductase [ 115 118 ]. Azo drugs like olsalazine, asacol, pentasa, balsalazide, azulfi dine, and salazopyrin for the treatment of ulcerative colitis and inflammatory bowel disease (IBD) [ 119 , 120 ] are pro‐drugs, having 5‐aminosalicylate (5‐ASA), a non-steroidal anti-inflammatory molecule, and an inert carrier are linked with an azo bond, in order to avoid their rapid adsorption [ 121 , 122 ].…”
Section: Modifications Of Drug Scaffold By Reductionmentioning
confidence: 99%
“…The bacterial genera Clostridium sp., Eubacterium sp., Clostridium leptum , C. paraputrificum , C. perfringens , and C. clostridiiforme exhibited nitroreductase and azoreductase activities in the human GI tract [ 101 – 104 ]. Misal and Gawai have classified azoreductase superfamily into five different groups, depending upon their preference for nicotinamide and flavin: (1) flavin-containing NADPH-dependent azoreductase [ 105 , 106 ], (2) flavin-containing NAD(P)H-dependent azoreductase [ 107 110 ], (3) flavin-containing NADH-dependent azoreductase [ 111 , 112 ], (4) flavin-containing NAD(P)H-dependent quinine oxidoreductases [ 113 , 114 ], and (5) flavin-free NAD(P)H-dependent azoreductase [ 115 118 ]. Azo drugs like olsalazine, asacol, pentasa, balsalazide, azulfi dine, and salazopyrin for the treatment of ulcerative colitis and inflammatory bowel disease (IBD) [ 119 , 120 ] are pro‐drugs, having 5‐aminosalicylate (5‐ASA), a non-steroidal anti-inflammatory molecule, and an inert carrier are linked with an azo bond, in order to avoid their rapid adsorption [ 121 , 122 ].…”
Section: Modifications Of Drug Scaffold By Reductionmentioning
confidence: 99%
“…That is, they were susceptible to reduction, and not easy to be oxidatively catabolized in aerobic environments (Ju and Parales 2010;Knackmuss 1996;Kulkarni and Chaudhari 2007). These similar reductive characteristics all supported that nitroreductases and azoreductases may originally derive from similar enzymatic systems (Hsueh et al , 2017Misal et al 2015;Cerniglia 1993, 1995;Rau and Stolz 2003).…”
Section: Electron-transfer-associated Biodecolorizationmentioning
confidence: 67%
“…In addition to the already mentioned TNT-degrading enzymes, azoreductases (AzoRs) can also participate in TNT degradation. Generally, AzoRs catalyze the cleavage of azo bonds (–N=N–) of aromatic azo dyes, but some of them have been reported to also have nitroreductase activity, including TNT reduction [ 104 , 105 , 106 ]. In addition, it has been demonstrated that the gene encoding AzoR1 in P. putida KT2440 is upregulated when this bacterium is grown in the presence of TNT [ 30 ].…”
Section: Resultsmentioning
confidence: 99%